Rice Production without Insecticide in Smallholder Farmer's Field - Ali, M. P.; Bari, M. N.; Ahmed, N.; Kabir, M. M. M.; Afrin, S.; Zaman, M. A. U.; Haque, S. S.; Willers, J. L. (Frontiers in Environmental Science, 2017)
Currently rice protection from insect pests solely depends on chemical pesticides which have tremendous impact on biodiversity, environment, animal and human health. To reduce their impact from our society we need to cut pesticide use from agricultural practices. To address this issue, we did experiment in order to identify realistic solutions that could help farmers to build sustainable crop protection system and minimum use of insecticides and thus minimizes the impact of pesticides in environment. Innovations developed jointly by farmers and researchers and evaluated for their potential to be adopted by more farmers. In this paper we tested four management practices jointly with farmers in smallholder farmer’s field in order to select best one. Four management practices were used namely, T1 = Prophylactic use of insecticide where insecticide was applied in rice field at every 15 days interval without judging the infestation level; T2 = Perching and simultaneously used sweeping and need base insecticide application; T3 = Perching only; and T4 = Farmer’s own practices. The results revealed that routine application of insecticides for crop protection is not mandatory which is commonly found at use in rice farmers. In our experiment, where prophylactic method or farmers used 3-4 times insecticides without judging the insect pests infestation level, the similar pest population was found when compared to the field where insecticide was not applied. Our management system reduced 75% insecticides use even the field was infested with insect pest. Predatory insects were higher than that of insecticide applied field. Refrain insecticide application up to 30-40 days after transplanting enhanced higher predatory population which might check the pest population in rice field. Our experimental results shows that proper manner of ecologically management system cut pesticide use without any yield penalty indicating T2 management system minimizes pest damage by increasing natural enemies and improves environment quality.